Practice Patterns and Outcomes Associated with Choice of Initial Vasopressor Therapy for Septic Shock - Fawzy, Ashraf (Crit Care Med, 2015)
OBJECTIVES: Clinical guidelines recommend norepinephrine as initial vasopressor of choice for septic shock, with dopamine suggested as an alternative vasopressor in patients at low risk for arrhythmias. We sought to determine practice patterns and outcomes associated with vasopressor selection in a large, population-based cohort of patients with septic shock that allows for assessment of outcomes in clinically important subgroups. DESIGN: We performed a retrospective cohort study to determine factors associated with choice of dopamine as compared with norepinephrine as initial vasopressor for patients with septic shock. We used propensity score matching to compare risk of hospital mortality based on initial vasopressor. We performed multiple sensitivity analyses using alternative methods to address confounding and hospital-level clustering. We investigated interaction between vasopressor selection and mortality in clinical subgroups based on arrhythmia and cardiovascular risk. SETTING: Enhanced administrative data (Premier, Inc) from 502 US hospitals during years 2010–2013. SUBJECTS: 61,122 patients admitted with septic shock who received dopamine or norepinephrine as initial vasopressor during the first two days of hospitalization. INTERVENTIONS: None MEASUREMENTS AND MAIN RESULTS: Norepinephrine (77.6%) was the most frequently used initial vasopressor during septic shock. Dopamine was preferentially selected by cardiologists, in the Southern US, at non-teaching hospitals, for older patients with more cardiovascular comorbidities, and was used less frequently over time. Patients receiving dopamine experienced greater hospital mortality (propensity matched cohort: N=38,788, 25% vs 23.7%; OR 1.08, 95% CI 1.02–1.14). Sensitivity analyses showed similar results. Subgroup analyses showed no evidence for effect modification based on arrhythmia risk or underlying cardiovascular disease. CONCLUSIONS: In a large population-based sample of patients with septic shock in the US, use of dopamine as initial vasopressor was associated with increased mortality among multiple clinical subgroups. Areas where use of dopamine as initial vasopressor are more common represent potential targets for quality improvement intervention.